Histogenesis of the metanephric glomeruli and nephrosis in goat - Gopinath, S; Singh, Yashwant (The Indian Journal of Animal Sciences, 2012)
This study, conducted on 65 goat embryos of different ages, showed the nephrogenic blastema, around ampullated end of the ureteric bud first in embryos of 12 mm CRL (21 days). It shifted peripherally along with the developing metanephric ducts by 24 mm CRL (36 days). The aggregates of blastema cells, noticed below ampullae of cortical ducts, elongated into S-shaped nephrogenic vesicles by 35 mm CRL (46 days). Their lower limb invaginated at distal end into the Bowman's capsule, while rest of the parts of lower and upper limbs of the nephrogenic vesicles differentiated into the nephrons in embryosof 45 mm CRL (50 days) to 70 mm CRL (56days). These gradually became coiled joined the duct system by 160 mm CRL (89 days) and attained structural maturity from 180 mm CRL (96 days) onwards. The metanephric glomeruli developed by ingrowth of interstitial mesenchyme into the Bowman's capsule showed signs of vascularity at 45 mm CRL (56 days) and simulated to the renal corpuscles of a mature kidney in goat embryos of 180 mm CRL (96 days) and beyond.